Haematological Changes in Chicks under the Influence of Fumonisins - K. NARASIMHA RAO; B. VIJAYAPAL REDDY; S. GIRISHAM; S.M. REDDY (International Journal of Pharma and Bio Sciences, 2010)
Haematological changes in chicks under the influence of fumonisins produced by Fusarium moniliforme was investigated. Fumonisins, besides causing dose dependent weight loss in chicks was responsible for decrease in serum protein, calcium, urea, albumins and bilirubins. On the other hand, an increase in activity of SGPT and SGOT was recorded.